ASUHAN KEPERAWATAN BERDASARKAN TEORI HENDERSON PADA KLIEN DENGAN ARTHROPLASTY LUTUT TOTAL: CASE SERIES - Aprillia Veranita; Masfuri; Liya Arista (Jurnal Mitra Kesehatan, 2023)
Patients post Total Knee Arthroplasty (TKA) will experience pain, mobility impairment, significant blood loss leading to anemia, and disruption of postoperative recovery. Method: This is a case report conducted on 13 patients with stage III and IV knee osteoarthritis and postoperative TKA. A knee prosthesis was used on the left knee. Nursing care was provided based on Henderson's 14 basic needs. Objective: The objective of this case report is to provide evidence-based elevation positioning using orthopedic cushions. The research results showed that all respondents experienced a decrease in drain production on the first day post-surgery, ranging from 100cc to 480cc (<500ml). About 84.6% of respondents had a postoperative Hb level of 10.4 g/dl. Range of motion (ROM) increased from 30 degrees to 90 degrees on the third day post-surgery. Conclusion: Postoperative elevation and flexion of the knee in TKA are effective in reducing blood loss and improving functional abilities, initiating rehabilitation, and early walking ability.